Non-bank Financial Institutions and Capital Markets in Turkey - World Bank (Washington, DC, 2013)
This study analyses the state of development, and prospects of future growth of Turkish non-bank financial institutions, and capital markets. Currently, credit markets in Turkey are dominated by banking, and capital markets are dominated by Government securities. Longstanding macro-economic instability, and inflation have discouraged investment in financial assets, and crowded out funding for the private sector. The resulting lack of depth, and breadth has made the financial sector vulnerable to shocks, resulting in repeated crises, and, has reduced its intermediation efficiency. To enhance the financial sector's capacity to support private sector development, and economic growth, and to reduce its vulnerability to shocks, non-bank sources of finance should be developed. The report identifies the key policy issues that should be addressed for this purpose. The discussion, and policy recommendations are structured around the following leading themes: a) mobilizing savings; b) building an institutional investor base, comprising insurance companies, private pension funds, and mutual funds; c) developing equity, debt, and derivative markets; d) developing leasing, factoring, and venture capital companies; and, e) strengthening confidence in financial markets through improved corporate governance, accounting and auditing standards, and practices, and, financial sector regulation, and supervision.